Pengaruh Green Product, Green Promotion, Dan Green Pricing Terhadap Keputusan Pembelian Konsumen Pada Produk Adidas ( Studi Kasus Pada Mahasiswa Universitas Islam Malang Fakultas Ekonomi dan Bisnis Prodi Manajemen Angkatan 2022 ) - M, Masriadi Ali; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This inquiry aims at analyze the influence of Green Product, Green Promotion, and Green Pricing on consumer purchasing decisions for Adidas products. The background of this research is based on increasing consumer awareness of environmental issues, which encourages companies to implement environmentally friendly marketing strategies. This study was conducted on students of the Faculty of Economics and Business, Management Study Program, University of Islam Malang, class of 2022, as the research population. The research method used was quantitative. Data were obtained by distributing questionnaires to 85 respondents selected using a purposive sampling technique. Data analysis was performedMultiple linear regression was employed to examine the impact of each independent variable on the dependent variable. The findings indicate that Green Product, Green Promotion, and Green Pricing collectively exert a significant effect on consumer purchasing decisions. Individually, Green Product and Green Promotion demonstrated an affirmative and material impact, whereas Green Pricing exhibited an affirmative yet insignificant role in purchase choices. These findings indicate that product sustainability and environmentally friendly promotions are more dominant factors in influencing students' purchasing decisions for Adidas products than price. Keywords: Green Product, Green Promotion, Green Pricing, buying decision